Effect of machining parameters on turning of VAT32® superalloy with ceramic tool - Bonhin, Eduardo Pires [UNESP]; David-Müzel, Sarah [UNESP]; De Souza, José Vitor Candido [UNESP]; Alves, Manoel Cléber De Sampaio [UNESP]; Ribeiro, Marcos Valério [UNESP] (Taylor & Francis, 2019)
The objective of this research was to study the machining of superalloy VAT32® using alumina-based ceramic tool without cutting fluid, applying different machining parameters to evaluate the surface finish of parts, vibration and main wear of tools. For this, a turning process with a linear trajectory of 30 mm was performed, in which were collected data vibration and surface roughness of the stretch, as well as wear and damage in the tools. The turning tests were performed utilizing cutting speeds of 270, 280 and 300 m/min, a feed of 0.10, 0.18 and 0.25 m/rev and a cutting depth of 0.50 mm. With results, it was identified that the feed influenced significantly both the vibration and the system, since the cutting speed influenced only the vibration. Being that the best results happened for the smaller feed and greater cutting speed. It concludes that the machining of superalloy VAT32® with ceramic tool introduced herself promising.
Keywords: alumina; chips; EDS; monitoring; Roughness; turning; VAT32®; vibration; wear